GENE-19. GAINING A BETTER UNDERSTANDING OF DNA METHYLATION FEATURES ASSOCIATED WITH SEX DIFFERENCES IN GLIOBLASTOMA. (5th November 2018) - Stetson, Lindsay; Lathia, Justin; Rubin, Joshua; Connor, James; Waite, Kristin; Berens, Michael; Barnholtz-Sloan, Jill
Abstract: Glioblastoma displays strong sexual dimorphism with male having an increased prevalence and poorer prognosis. While sex based methylation differences in the MGMT promoter have been described in GBM patients, we expanded on these findings with a full genome interrogation of sex-based DNA methylation differences in GBM patients (n = 56 females, n = 77 males). Using Illumina 450k DNA methylation data from The Cancer Genome Atlas (TCGA), we found 359 probes and 12 regions significantly differentially methylated between males and females (sex chromosomes were excluded from the analysis). Males had three times the number of probes significantly differentially hypermethylated than females. In males hypermethylated probes occurred in known enhancer regions at a rate of 4:1 as compared to females. Areas of hypermethylation in females predominately (65%) occurred in CpG islands. An analysis of DNA motif binding sites showed multiple zinc finger transcription factor binding sites located in genomic regions hypermethylated males. Binding sites of KLF6, an important tumor suppressor known to increase p21 expression through a p53 independent pathway, were located in areas significantly hypermethylated in males. We established significant correlation between expression of p21 and methylation of KLF6 binding sites. These findings provide a potential biological basis for our previous observation of increased p21 activity and cell cycle arrest in response to DNA damage in female, but not male GBM astrocytes. Additionally, we found that NFAT5 transcription factor binding sites were significantly hypermethylated in females. These results point to possible protective biology in females, where repression of NFAT5 results in reduced integrin-induced cell dispersion and increased p21 expression results in decreased proliferation. Understanding the molecular basis for sex-based differences will improve our understanding of tumor biology and pave the way for novel diagnostics and a personalized approach for the development of more effective therapies.